2023
DOI: 10.1039/d2ce01666d
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties and optical absorption of oxygen vacancy cluster defects in KDP crystals: hybrid density functional theory investigation

Abstract: The oxygen vacancy, hydrogen vacancy and potassium vacancy are the common intrinsic point defects in the potassium dihydrogen phosphate (KDP) crystals and can combine to form cluster defects. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The force convergence criterion for structural relaxation was set to 0.01 eV Å −1 . 17,31 The electronic wave functions were expanded as plane waves using an energy cutoff of 680 eV. 32–35…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The force convergence criterion for structural relaxation was set to 0.01 eV Å −1 . 17,31 The electronic wave functions were expanded as plane waves using an energy cutoff of 680 eV. 32–35…”
Section: Computational Detailsmentioning
confidence: 99%
“…In our previous study, the Heyd–Scuseria–Ernzerhof (HSE06) 36–38 hybrid functional method was more suitable for calculating the electronic properties of the KDP crystals because the band gap obtained using this calculation method (7.2 eV 17,21 ) was similar to the experimental value (∼7.6 eV 39 ). 31,40 Therefore, the energetic, electronic and optical properties were analyzed using the HSE06 method. The H 1s 1 , P 3s 2 3p 3 , O 2s 2 2p 4 , K 4s 1 and Cr 3d 5 4s 1 states were treated as valence electrons.…”
Section: Computational Detailsmentioning
confidence: 99%
“…10,17 Therefore, it is significant to research the influence of point defects on KDP crystals to enhance device quality and performance. 15,18 Negative divalent interstitial oxygen has been studied, which leads to the ejection of two H ions from their normal position to form two hydrogen vacancies and one H 2 O molecule, and this can be used to explain the reported decomposition of KDP during laser-induced breakdown. 15 Past studies have shown the effect of interstitial hydrogen and hydrogen vacancies on the KDP crystal structure and the induced defect states in the band gap are dependent on their charge states.…”
Section: Introductionmentioning
confidence: 99%
“…16 The electronic and optical properties of oxygen vacancy defects have also been investigated. 18 These defects will lead to a reduction in band gap and induce additional absorption peaks at 6.4 eV and large distortions in the H–O bond, all of which will lower the laser-induced damage threshold. 18 Numerous studies have found that bonds have a tremendous effect on the optical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation